Independent and combined effect of serum copper and folate on depression: cross-sectional data from the NHANES 2011–2016 - Liu, Mengqing; Wang, Gang; Jiang, Chongfei (Frontiers in Nutrition, 2024)
Depression is a widespread mental health condition that can impact both mental and physical well-being. Prior research has shown that high levels of copper in the blood and low levels of folate are linked to depression. This study aimed to explore whether serum folate levels, independently or in combination with serum copper levels, associated with the risk of depression.Data from participants aged 18 to 80 years in the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016 were analyzed to examine the role of trace elements. Depression was assessed using the nine-item Patient Health Questionnaire (PHQ-9). Logistic regression analyses were employed to evaluate the main effect of serum copper and folate levels on depression. Three indices, including the relative excess risk of interaction (RERI), attributable proportion of interaction (API), and synergy index (SI), were used to analyze the interaction effect.Among the 4847 participants selected for this study, 429 (8.9%) had PHQ-9 scores above 10, which we defined as having depressive symptoms. After adjusting for all confounding factors, higher serum copper levels [≥15.5 vs.＜15.5μmol/L, odds ratio (OR): 1.54; 95% confidence intervals (CI):1.18-2.11] and folate deficiency (folate ≥ 53.7 vs.＜53.7μmol/L, OR: 1.44; 95% CI:1.21-2.10) were associated with an increased risk of depression. Patients with both higher serum copper levels and folate deficiency (OR: 2.11; 95% CI:1.43-3.14) had the highest risk of depression 4 / 33 than other levels. High copper levels and low folate levels are associated with the occurrence of depression symptoms, and there may be a synergistic effect between them (SI: 1.65; 95% CI:1.49-4.76), with this interaction accounting for 19% of depression cases (API:0.19; 95% CI:0.01-0.54).There may be a synergistic interaction between high copper levels and low folate levels associated with increasing risk of depression. Further population-based interventional studies are needed to confirm whether folic acid supplementation is effective in preventing depression in individuals with high blood copper levels.